P14.24 Estimating survival outcomes in elderly (70+ years) patients with primary glioblastoma. (9th September 2021) - Zorman, M J; Webb, P; Nixon, M; Sravanam, S; Honeyman, S; Nandhabalan, M; Apostolopoulos, V; Stacey, R; Hobbs, C; Plaha, P
Abstract: BACKGROUND: Elderly patients with glioblastoma are perceived to face a poor prognosis, with perceptions around older age and a relative lack of randomized data raising a concern about their undertreatment. The EANO guidelines recommend >70-year-old patients with good performance status to undergo maximal safe resection followed by hypofractionated (40 Gy in 15 fractions, i.e. RT40/15) radiotherapy with or without concurrent and adjuvant Temozolomide (TMZ), depending on MGMT promoter methylation. This study evaluated the relative survival impact of biological, histological, surgical and oncological factors and aimed to devise a scoring system to estimate the survival of elderly glioblastoma patients, with an aim to more accurately guide treatment in this cohort. METHODS: The records of 169 elderly (≥70 years) patients with a new diagnosis of IDH-wild type glioblastoma were retrospectively examined for gender, age, WHO performance status (PS), comorbidities, MGMT methylation, surgical intervention and chemoradiation regime. The adjusted survival impact of these factors was determined using Cox proportional hazards model and used to devise a two-stage scoring system to estimate survival of patients at the stage of surgical (Elderly Glioblastoma Surgical Score, EGSS) and oncological management (Elderly Glioblastoma Oncological Score, EGOS). RESULTS: The overall median survival (MS) of the cohort was 28.8 weeks. Subtotal resection (MS=27.7 weeks, 95%CI 24.1–31.6 weeks, HR=0.58) and gross-total resection (MS=77.8 weeks, 95%CI 67.0–88.6 weeks, HR=0.36) were associated with significant overall survival benefit compared to biopsy alone (MS=18.2 weeks, 95%CI 15.7–20.7 weeks, HR=5.23), p<0.05. Hypofractionated radiation with Temozolomide (RT40/15+TMZ, MS=60.9 weeks, 95%CI 49.9–71.8 weeks, HR=0.13) was non-inferior to the Stupp protocol (RT60/30+TMZ, MS=50.6 weeks, 95%CI 32.4–66.7 weeks, HR=0.11), p=0.72. Negative prognosticators included age above 75 years, biopsy alone and no chemoradiotherapy. Subgroup analysis revealed that MGMT unmethylated 70–75 year old patients who received the Stupp protocol had significantly improved overall survival (MS=57.6 weeks, 95%CI 27.7–88.1 weeks) compared to standard of care RT40/15 alone (MS=29.7 weeks, 95%CI 7.1–51.6 weeks), p=0.002. EGSS and EGOS scores estimated survival with 65% and 73% accuracy, respectively. CONCLUSION: When appropriate and safe, a subgroup of elderly glioblastoma patients may benefit from more aggressive surgical and oncological management. The proposed EGSS and EGOS scores takes into account important prognostic factors to help guide which patients should receive such treatment.